2017
DOI: 10.1007/978-3-319-51908-1_31
|View full text |Cite
|
Sign up to set email alerts
|

Medicating Patients During Extracorporeal Membrane Oxygenation: The Evidence is Building

Abstract: This article is one of ten reviews selected from the Annual Update in Intensive Care and Emergency Medicine 2017. Other selected articles can be found online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…Most β‐lactams are hydrophilic molecules, primarily eliminated by the kidneys, and have low to moderate protein binding (exception ceftriaxone), making these agents highly susceptible to pharmacokinetic changes from critical illness and, potentially, from the addition of an extracorporeal circuit. Significant losses of meropenem, a highly lipophilic carbapenem, were observed in some studies, whereas more recent ex vivo studies noted minimal loss of cephalosporins and carbapenems in the ECLS circuit . A retrospective case‐control study observed no significant differences in pharmacokinetics with either piperacillin‐tazobactam or meropenem in patients managed with or without ECLS .…”
Section: Specific Ecls Management Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most β‐lactams are hydrophilic molecules, primarily eliminated by the kidneys, and have low to moderate protein binding (exception ceftriaxone), making these agents highly susceptible to pharmacokinetic changes from critical illness and, potentially, from the addition of an extracorporeal circuit. Significant losses of meropenem, a highly lipophilic carbapenem, were observed in some studies, whereas more recent ex vivo studies noted minimal loss of cephalosporins and carbapenems in the ECLS circuit . A retrospective case‐control study observed no significant differences in pharmacokinetics with either piperacillin‐tazobactam or meropenem in patients managed with or without ECLS .…”
Section: Specific Ecls Management Considerationsmentioning
confidence: 99%
“…If lower ventilator settings confer a lesser risk of VILI, then removal of the ventilator would eliminate the risk of the ventilator altogether. In practice, endotracheal extubation is the preferred approach for those awaiting lung transplantation, where being awake, mobile, and free of ventilator‐associated complications are all vital to maintaining transplant candidacy . In patients with ARDS, an awake extubated strategy would certainly be preferred from the perspective of avoiding ventilator complications, but it is often difficult to identify those patients in whom such a strategy will be tolerated while still maintaining sufficient gas exchange.…”
Section: Specific Ecls Management Considerationsmentioning
confidence: 99%
See 3 more Smart Citations